Mitos lelaki ideal dalam novel Mustika Zakar Celeng karya Adia Puja: studi semiotika Roland Barthes - Wijaya, M. Isnaini; Karkono, Karkono (Universitas Mulawarman, 2025)
The novel Mustika Zakar Celeng explores the struggle between husband and wife in achieving inner satisfaction. The husband is willing to do anything to make his wife happy and preserve their household. The heroism depicted in the novel aligns strictly with male ideals. This study aims to describe the myths of modern humans, particularly the construction of the ideal man. This study uses Roland Barthes' semiotic method to uncover the myth of the ideal man, supported by Janet Saltzman Chafetz's masculinity theory. It adopts a qualitative approach with a descriptive design. The novel Mustika Zakar Celeng serves as the primary source of analysis. The data is a narrative that reveal the myth of the ideal man. Data collection was conducted through reading and note-taking. The analysis follows Miles and Huberman's interactive framework, involving data reduction, data presentation, and conclusion. The results show that the ideal man has five criteria: (1) a masculine appearance, (2) prowess in intimate matters, (3) financial stability, (4) inner beauty, and (5) loyalty to his partner. These criteria align with Janet Saltzman Chafetz's masculinity aspects, emphasizing that a man must embody these traits to be considered ideal.